Fernando Zobel and the Making of the Ateneo Art Gallery: Modern Art, Postcolonial Statehood, and the Utopian Imagination in Twentieth-Century Philippines - Veric, Charlie Samuya (Archīum Ateneo, 2017)
Fernando Zobel de Ayala y Montojo is a towering figure in modern Filipino art and criticism. An award-winning artist and an astute theorist, he founded the Ateneo Art Gallery in 1960. Six years later, he established the Museum of Spanish Abstract Art in Cuenca, Spain. Art histories in the Philippines and Spain are certainly unimaginable without Zobel, yet very little has been written about him. With the exception of a handful of articles, not much art historical discussion of Zobel exists, especially in the context of the rise of Filipino modern art and the development of Philippine postcolonial state as utopian phenomena. The essay fills this gap. In particular, I will argue that an understanding of Zobel and his influence must consider the mutual emergence of modern art and postcolonial statehood, events that cannot be dissociated from utopian sentiments defining the historical project of decolonization in the middle of the twentieth century. Moreover, I will argue that Zobel may be considered as a decolonizing voice, a touchstone in postcolonial Filipino art criticism. This essay not only fills a significant gap in the scholarship on Zobel but also hopes to reframe our understanding of modern art in the Philippines.